From Data into Action : The Impact of Gender Analysis on Policy and Programming - de Paz Nieves, Carmen; Muller, Miriam (Washington, DC: World Bank, 2021)
The ultimate objective of gender analysis is to inform programs and policies that contribute to closing persistent gaps. However, the specific impact of gender analysis and advice activities is not always evident or measured. There is growing interest among development partners, including the World Bank, in better understanding and systematizing the associations between data and reforms in this area. Is the increasing amount of knowledge generated over the last years translating into actual programmatic and policy change to close gender gaps If so, what are the factors that can help to move from diagnostics and technical assistance into action Based on a review of recent successful experiences of the Poverty and Equity Global Practice at the World Bank Group, this note summarizes emerging lessons that can help to start addressing these questions.